Significance of Negaraku as a national symbol: a review of national identity concept - Siti Nurkhalilah Liana; Azizan Zainuddin; Anida Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2024)
The existence of national symbols plays a crucial role in reflecting the identity of a nation. The national anthem is one of the national symbol categories that are commonly used by every nation in this world. The combination of syntactic (musical) and semantic (lyrical) structure make it unique from any other national symbols. Despite of tangibility of other national symbols, the national anthem is intangible, and the lack of transient makes it stronger towards the emotional attachment. Negaraku also faces the same problem as there is a lack of understanding regarding the significance of the national anthem as a symbol of national identity. The continuous issues of contempt regarding Negaraku from 1957 until 2022 show the lack of understanding of the anthem itself as a symbol of national identity. Therefore, this paper aims to emphasize the significance of Negaraku as a symbol of national identity as a foundation of knowledge for fellow citizens about Malaysia. An integrative literature review is used to analyze the significance of Negaraku towards national identity discussion. The analysis will review various sources of relevant information from international and local references which cover books, journals, websites as well as newspaper cutting. Based on the analysis drawn it proves that Negaraku textual structures indicate a direct interpretation of national identity through historical and cultural elements in political and economic perspectives. In conclusion, the conceptual discussion through Negaraku contextual analysis can widen the social sciences area through anthemology studies in Malaysia.